Are Postprandial Bile Acid Levels Helpful in Predicting Perinatal Complications in Patients with Intrahepatic Cholestasis of Pregnancy? - Kudret Erkenekli; Can Tekin iskender; Hasan Onur Topcu; Tugba Ensari; Dilek Uygur; Nuri Danisman (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Purpose: To determine the outcomes of Iintrahepatic cholestasis of pregnancy and the role of postprandial serum bile acid levels in the prediction of perinatal complications. Material and Methods: This retrospective study consisted of 103 patients with intrahepatic cholestasis of pregnancy between January 2008 and June 2013. Maternal age, obstetric history, pregnancy outcome, maternal and neonatal complications, ursodeoxycholic acid treatment during pregnancy and serum laboratory tests were retrieved from patients' medical records. Receiver operating characteristic analysis was used to evaluate the performance of fasting and postprandial serum bile acid levels to predict perinatal complications. Results: Gestational diabetes and preterm delivery occurred more frequently in patients with intrahepatic cholestasis of pregnancy patients. The rate of primary cesarean delivery was more common in in patients with intrahepatic cholestasis of pregnancy patients. The rate of growth-restricted infants was higher in the patients who received ursodeoxycholic acid. Nenoatal intensive care unit admissions and overall neonatal complications, as well as spontaneous preterm deliveries, were similar among in patients with intrahepatic cholestasis of pregnancy regardless of ursodeoxycholic acid therapy. In the receiver operating characteristic analysis, the area under curve values for postprandial and fasting bile acids to predict neonatal complications were 0.64 and 0.70, respectively. Conclusion: Intrahepatic cholestasis of pregnancy patients increases certain perinatal complications, such as preterm deliveries and neonatal morbidity. Postprandial serum bile acid levels are inferior to fasting serum bile acid levels in the prediction of obstetric complications. ursodeoxycholic acid does not seem to improve perinatal outcomes. [Cukurova Med J 2015; 40(2.000): 212-220]